2004
DOI: 10.1007/s11745-004-1292-5
|View full text |Cite
|
Sign up to set email alerts
|

Sterol metabolism in the opportunistic pathogen Pneumocystis: Advances and new insights

Abstract: Pneumocystis can transiently colonize healthy individuals without causing adverse symptoms, and most people test positive for exposure to this organism early in life. However, it can cause Pneumocystis pneumonia (PcP) in people with impaired immune systems and is a major cause of death in HIV/AIDS. Although it has close affinities to the Ascomycetes, Pneumocystis has features unlike those of any single group of fungi. For example, Pneumocystis does not synthesize ergosterol, which is consistent with the ineffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…The lack of a long-term in vitro culture indicates that some crucial nutrients are missing or undersupplemented in the culture medium. Previous metabolic studies indicated that the pathogen does not synthesize ergosterol and has to scavenge cholesterol from its host to thrive (6). More recent genome-sequencing studies pointed out that the fungus has dramatic underrepresentation of amino acid synthesis pathways (7).…”
Section: Introductionmentioning
confidence: 99%
“…The lack of a long-term in vitro culture indicates that some crucial nutrients are missing or undersupplemented in the culture medium. Previous metabolic studies indicated that the pathogen does not synthesize ergosterol and has to scavenge cholesterol from its host to thrive (6). More recent genome-sequencing studies pointed out that the fungus has dramatic underrepresentation of amino acid synthesis pathways (7).…”
Section: Introductionmentioning
confidence: 99%
“…Obligate parasitism has been suggested on the basis of their strict host specificity [5]–[7], patterns of co-evolution with hosts [5], [8], genetic flexibility of chromosome ends responsible for expression of a single antigen encoding gene [9], [10], and the fact that they scavenge cholesterol from their host to build their own membranes [11]. Scavenged cholesterol is found in the membrane together with specific sterols that Pneumocystis synthesizes de novo [12]. However, the issue of whether Pneumocystis species also have a free-living form in nature remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the fungus contains the incomplete steroid biosynthesis pathway, missing Erg2, Erg3, and Erg5 enzymes downstream of the pathway. This indicates that it cannot synthesize ergosterol from precursors and has to scavenge cholesterol from its host, which has been previously pointed out in other studies [10,11], and may explain the fact that the pathogen is not susceptible to antifungal drugs targeting this pathway, such as azole-based therapeutics. The detailed per pathway information derived using EC2KEGG with entailed highlighted KEGG Pathway maps can be found at http://pgp.cchmc.org/.…”
Section: Resultsmentioning
confidence: 75%